2021
DOI: 10.19044/esj.2021.v17n17p335
|View full text |Cite
|
Sign up to set email alerts
|

Screening phytochimique, dosage des polyphénols et détermination de l’activité antioxydante de deux plantes antihypertensives du Niger

Abstract: Acanthospermum hispidum Dc. et Ximenia americana L. sont largement utilisées en Afrique subsaharienne pour le traitement traditionnel de plusieurs pathologies, dont l’hypertension artérielle. L'objectif du présent travail est de déterminer l’activité antioxydante des extraits bruts de ces plantes, ainsi que les molécules qui leurs confèrent ces propriétés. A cet effet, les parties aériennes d’A. hispidum récoltées à Niamey et l’écorce de tronc de X. americana récoltée à Gaya ont été extraites avec des solvants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…This could support the way local people prepare Hibiscus Sabdarifa juices, to better benefit from the benefits of these chemical compounds. Indeed, these compounds were also known for their anti-free radical scavenging properties, helping to fight against oxidative stress (Ali et al, 2005;Djamilatou et al, 2021). The latter is responsible for many adverse health effects, as it has been linked to the development of complications in several diseases such as diabetes, hypertension, cancer and neurodegenerative diseases (Giacco et al, 2010;Jay et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This could support the way local people prepare Hibiscus Sabdarifa juices, to better benefit from the benefits of these chemical compounds. Indeed, these compounds were also known for their anti-free radical scavenging properties, helping to fight against oxidative stress (Ali et al, 2005;Djamilatou et al, 2021). The latter is responsible for many adverse health effects, as it has been linked to the development of complications in several diseases such as diabetes, hypertension, cancer and neurodegenerative diseases (Giacco et al, 2010;Jay et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies conducted on species of the same genus (Ferreira-Filho et al, 2020) and on other Bauhinia species (Aliyu et al, 2009;Chew et al, 2011) resulted in the same finding. In addition, experimental and clinical studies have shown that phytophenols enhance endothelial formation of vaso-protective factors such as nitric oxide (NO) (Auger and Valerie, 2014;Djamilatou et al, 2021).…”
Section: Tp Content Of Organs Of B Monandramentioning
confidence: 99%
“…Under normal conditions, aerobic metabolism in mammals generates substances called ROS that are acting in small amounts in physiological processes [ 2 ]. However, excess production of ROS can become toxic to major components of the cell, including lipids, proteins, and nucleic acids and therefore leads to oxidative stress [ 3 ]. Oxidative stress is involved in various diseases such as cardiovascular diseases, cancer, diabetes, neurodegenerative diseases, and in the aging process [ 4 ].…”
Section: Introductionmentioning
confidence: 99%